2016
DOI: 10.1038/srep29022
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and identification of candidate genes from the chitinase gene family for Verticillium dahliae resistance in cotton

Abstract: Verticillium dahliae, a destructive and soil-borne fungal pathogen, causes massive losses in cotton yields. However, the resistance mechanism to V. dahilae in cotton is still poorly understood. Accumulating evidence indicates that chitinases are crucial hydrolytic enzymes, which attack fungal pathogens by catalyzing the fungal cell wall degradation. As a large gene family, to date, the chitinase genes (Chis) have not been systematically analyzed and effectively utilized in cotton. Here, we identified 47, 49, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 67 publications
(119 reference statements)
5
39
0
4
Order By: Relevance
“…Gene structure analysis showed that Gh4CL genes of the same class share a similar intron-exon structure (Fig. 2b), similar to the observations made in other gene families [40,41].…”
Section: Discussionsupporting
confidence: 85%
“…Gene structure analysis showed that Gh4CL genes of the same class share a similar intron-exon structure (Fig. 2b), similar to the observations made in other gene families [40,41].…”
Section: Discussionsupporting
confidence: 85%
“…Gene structure analysis showed that Gh4CL genes of the same class share a similar intron-exon structure (Fig. 2b), similar to the observations made in other gene families [30][31][32].…”
Section: Discussionsupporting
confidence: 84%
“…Analysis method of data model expression as follows: if the value of log 2 FPKM is more than 1, we consider it to be expressed and if the value of log 2 FPKM is less than or equal to 1, we consider it not to be expressed (Xu et al 2016a, b). …”
Section: Methodsmentioning
confidence: 99%